Disability Inclusive Disaster Risk Reduction and Management: Assessing Vulnerabilities and Local Responses in Maasin City, Philippines - Kristoper Rex Oraiz; Elmee Joy Oraiz (ASEAN Social Work Journal, 2025)
Age and Disability Consortium. (2018). Minimum standards for age and disability inclusion in humanitarian action. https://adstandards.org/